2015
DOI: 10.1039/c5ew00061k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disinfection by-products during ballast water treatment with ozone, chlorine, and peracetic acid: influence of water quality parameters

Abstract: Differences in water quality from freshwater to seawater alter disinfection by-product formation during disinfection of ballast waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 45 publications
5
71
0
Order By: Relevance
“…in sea or brackish water was able to form CHBr 3 (up to 920 µg/L) and CHBr 2 Cl (up to 110 µg/L), whereas no formation of CHCl 3 or CHBrCl 2 was observed [205]. This is due to the much lower rate constant for the PAA reaction with chloride compared to the reaction with bromide [205].…”
Section: Ch 3 Coooh + Ch 3 Oh → Ch 3 Cooh + Hcho + H O(14) Ch 3 Cooohmentioning
confidence: 67%
See 3 more Smart Citations
“…in sea or brackish water was able to form CHBr 3 (up to 920 µg/L) and CHBr 2 Cl (up to 110 µg/L), whereas no formation of CHCl 3 or CHBrCl 2 was observed [205]. This is due to the much lower rate constant for the PAA reaction with chloride compared to the reaction with bromide [205].…”
Section: Ch 3 Coooh + Ch 3 Oh → Ch 3 Cooh + Hcho + H O(14) Ch 3 Cooohmentioning
confidence: 67%
“…However, only very modest or undetectable amounts of chlorinated and brominated DBPs (e.g., chlorophenols, bromophenols, or total trihalomethanes) have been observed with PAA under typical fresh water or wastewater disinfection conditions [120,127,169,170,201]. No formation of bromate (BrO 3 -) was detected in surface or reclaimed water [169] or in saline water [205]. However, it has been found that an increase in the PAA or halogenide concentration promotes the formation of halogenated DBPs [204].…”
Section: Ch 3 Coooh + Ch 3 Oh → Ch 3 Cooh + Hcho + H O(14) Ch 3 Cooohmentioning
confidence: 92%
See 2 more Smart Citations
“…Chemical BWTSs that apply oxidative treatment have been shown to produce a variety of so-called disinfection by-products (DBPs) including trihalomethanes, halogenated acetic acids and bromate (Delacroix et al, 2013;Werschkun et al, 2014;Shah et al, 2015). The generally proposed mechanism for generating DBPs is the reaction of oxidants such as chlorine and ozone with organic and inorganic substances, such as bromide (Br-) and iodide (I-), in the water via the formation of hypobromous (HOBr) and hypoiodous (HOI) acid.…”
Section: Ballast Water Treatmentmentioning
confidence: 99%